Mental well-being among children in foster care: The role of supportive adults. (July 2019) - Magee, Carly; Guhn, Martin; Schonert-Reichl, Kimberly A.; Oberle, Eva
Abstract: Objectives: Few studies have examined predictors of positive development among children currently in foster care. We examined associations between perceived support from adults in three developmental contexts (home, school and neighbourhood) and mental well-being (life satisfaction, self-concept, optimism) among grade four children living with foster parents in British Columbia (B.C.), Canada. Methods: The sample was comprised of children who completed the Middle Years Development Instrument (MDI) in B.C. schools between 2011 and 2016 and who reported living with a foster parent ( N  = 211). Hierarchical linear regression analysis was used to examine individual and joint associations between adult support variables and mental well-being indicators, controlling for gender, age and ESL status. Results: Results showed that perceived support from adults at home and school were both individually, positively associated with all three well-being indicators, while perceived support from adults in the neighbourhood was not individually associated with any mental well-being indicators. Conclusion: This study indicated that perceived support from adults at home and school are individually associated with mental well-being among children in foster care during middle childhood. Policy aimed at improving the well-being of children in care should be considered for both in child welfare and school systems. Highlights: Perceived support from adults was positively associated with mental well-being among children in foster care Perceived support from adults at home and school were both individually associated with mental well-being Perceived support from adults in the neighbourhood was not individually associated with mental well-being.